(3GOGQI GddhLSJjGJ (B:s (3JNWjW hJfXje SdSdI GdGeOGO (B/s - (3HGdh, QhfGdO GJTs ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2006)
(3dhLjSJjGJ GdGYeGd h GSJQGJjLjI GddhLjSJjGJ h GdJNWjW GVGaI Gdi GdefJL GddhLjSJj h GdNOeI GddhLjSJjI ddYejd h eYGdLI GdWdHGJ h fXe GdeYdheGJ (B,(3cPdc CSGSjGJ Gdfbd h bQGQGJg h bQGQGJg h cPG fXGe GdJNRjf h GdefGhdI h GdJfHD HGdeJWdHGJ GddhLjSJjI h GdbQGQGJ GdNGUI HSjGSI GdeNRhfh GdbQGQGJ GdNGUI HLOhdI GdGeOGO h GdeTJQjGJ(B, (3GdbQGQGJ GdeJYdbI HGdJNRjf h GdefGhdI(B, (3GdbQGQGJ GdNGUI HJMOjO ehbY GdefTBJ (B,(3YedjI JNWjW GdTHcI h cPG JfXje GddhLjSJjGJ h aj GdGNjQ GdQbGHI h GdeQGLYI dddhLjSJjGJs
(3edGMb U(B.845,(3eQGLY U(B.851s
Keywords: (3GdJNWjWs; (3GdQbGHIs; (3GdfJXjes